2022
DOI: 10.1080/13880209.2022.2096644
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic acid B inhibits myocardial I/R-induced ROS generation and cell apoptosis by regulating the TRIM8/GPX1 pathway

Abstract: Context Salvianolic acid B (SalB) can attenuate myocardial ischemia/reperfusion (I/R) injury, but the mechanisms are not entirely known. Objective Our study investigates if SalB protects cardiomyocytes against I/R injury by regulating Tripartite motif (TRIM) protein. Materials and methods AC16 cardiomyocytes were treated with I/R, and then with SalB (10, 25 and 50 μM) for 24 h, while control cells were cultured under normal conditions. Female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Further, we explored the different pharmacodynamic effects of DHI, PM, and SM on MI/RI. Studies have widely reported the anti-inflammatory and antioxidant effects of the secondary metabolite fractions that were primarily composed of phenolic acids, including salvianolic acid B [34][35] , lithospermic acid [36] , rosmarinic acid [37] , salvianolic acid A [38] , and protocatechuic aldehyde [39] . However, the effects and material basis of the primary metabolites with low polarity, mainly consisting of sugars and amino acids, have not been studied in depth.…”
Section: Discussionmentioning
confidence: 99%
“…Further, we explored the different pharmacodynamic effects of DHI, PM, and SM on MI/RI. Studies have widely reported the anti-inflammatory and antioxidant effects of the secondary metabolite fractions that were primarily composed of phenolic acids, including salvianolic acid B [34][35] , lithospermic acid [36] , rosmarinic acid [37] , salvianolic acid A [38] , and protocatechuic aldehyde [39] . However, the effects and material basis of the primary metabolites with low polarity, mainly consisting of sugars and amino acids, have not been studied in depth.…”
Section: Discussionmentioning
confidence: 99%
“…SAB has been shown to effectively attenuate cardiovascular injuries by reducing the expression of related inflammatory factors, inhibiting apoptosis, and reducing oxidative stress in experimental settings (117). Numerous studies have demonstrated the cardiomyocyte protective effects of SAB during myocardial ischemia-reperfusion injury (MIRI) and its ability to reduce oxidative stress-induced damage (118). Similar to SAA, SAB also reduces post-ischemic LDH leakage (119).…”
Section: Salvianolic Acid Bmentioning
confidence: 99%
“…For example, in the study of traumatic brain injury in mice, the lack of GPX1 increased the attack of ROS on hippocampal neurons, causing damage to post-traumatic memory function (Kim et al, 2022). In studies of myocardial ischemia-reperfusion injury, GPX1 KO exacerbated oxidative stress injury during myocardial ischemia-reperfusion (Lu et al, 2022). In addition, in the study of oxidative stress injury in cochlear spiral ganglion neuronal cells (SGNs), it was found that when GPX1 is knocked out, the oxidative stress damage of SGNs by peroxynitrite is aggravated, resulting in loss of SGNs and loss of hearing (Wang et al, 2022).…”
Section: Gpx1mentioning
confidence: 99%